Nucleoside-modified mRNA vaccination partially overcomes maternal antibody inhibition of de novo immune responses in mice - Willis, Elinor; Pardi, Norbert; Parkhouse, Kaela; Mui, Barbara L; Tam, Ying K; Weissman, Drew; Hensley, Scott E (Science translational medicine, 2020)
Maternal antibodies provide short-term protection to infants against many infections. However, they can inhibit de novo antibody responses in infants elicited by infections or vaccination, leading to increased long-term susceptibility to infectious diseases. Thus, there is a need to develop vaccines that are able to elicit protective immune responses in the presence of antigen-specific maternal antibodies. Here, we used a mouse model to demonstrate that influenza virus-specific maternal antibodies inhibited de novo antibody responses in mouse pups elicited by influenza virus infection or administration of conventional influenza vaccines. We found that a recently developed influenza vaccine, nucleoside-modified mRNA encapsulated in lipid nanoparticles (mRNA-LNP), partially overcame this inhibition by maternal antibodies. The mRNA-LNP influenza vaccine established long-lived germinal centers in the mouse pups and elicited stronger antibody responses than did a conventional influenza vaccine approved for use in humans. Vaccination with mRNA-LNP vaccines may offer a promising strategy for generating robust immune responses in infants in the presence of maternal antibodies.